Accountability at the Local Level in Fragile Contexts: Bangladesh Case Study. (23rd September 2013) - Buchmann, Daniela Christina
Summary: This paper, part of an IDS and Helvetas Swiss Intercooperation research project, is about the promotion of accountability at the local level in Bangladesh. By exploring in this context the legal grounds for accountability, the role of social hierarchies based on gender, education, family and wealth, and the impact of political alliances on accountability, the paper focuses on the social and political factors which may enable or prevent emerging accountability practices. The accountability practices studied in this context are local networks formed and supported by SDC's local governance programme Sharique. These networks strive to emerge as catalysts of social and economic development as well as good governance in Bangladesh. Composed of local governance actors, local networks bring information, spaces for participation and opportunities for oversight closer to citizens in rural Bangladesh, making it easier for them to benefit from accountability options provided by their government. This paper elaborates the strategy Sharique applies to help networks take on this role in a socially and politically divided context. It maintains that this strategy contributes to a transfer of power from a powerful individual to a group, setting off a process of collectivisation and affecting each member's role in engaging in local development and promoting accountability. However, the paper also draws attention to disparities that persist between members of the networks studied, with respect to different elements of accountability. It argues that the active promotion of all elements of accountability is necessary for Sharique to reach out to all populations through this initiative. It concludes that the success of accountability practices both on a conceptual and applied level is subject to clear differentiation between elements of accountability, which avoids relying on assumed casual connections between them.